KEPUTUSAN ETIS PEKERJA MEDIA DALAM MENGHADAPI KEKUATAN PEMILIK MEDIA - Fariza Yuniar Rakhmawati (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2014)
Abstract Concentration of media ownership in Indonesia is considered problematic be- cause the owners of the media as well as a political actor. Activity owners of media conglomerates in the world of politics is feared to threaten the exist- ence of the media as the fourth pillar of democracy. The independence of me- dia workers into the hope that the media remains in the public interest. Ethics deontological, teleological ethics and virtue ethics as a guide ethical decision autonomous realization of media workers. Based on deontological ethics, me- dia workers must be ethical because it conveys reliable information ethically. Basic code of ethics for media workers in Indonesia is a professional organiza- tion code of ethics and code of conduct. Teleological ethics based media work- ers need to pay attention to the public interest. Media workers is important to be prioritized for the public interest over other interests, because the media is a public space that allows the creation of many voices and express a wide range of different views. Based on virtue ethics perspective, the content that is broadcast in the media is a reflection of the values espoused individual media workers. Abstrak Pemusatan kepemilikan media di Indonesia dipandang bermasalah karena pemilik media sekaligus menjadi aktor politik. Aktivitas pemilik konglomerasi media dalam dunia politik dikhawatirkan mengancam eksistensi media sebagai pilar keempat demokrasi. Independensi pekerja media menjadi harapan agar media tetap mengutamakan kepentingan masyarakat. Etika deontologi, etika teleologi dan etika keutamaan menjadi panduan realisasi otonomi keputusan etis pekerja media. Berdasarkan etika deontologi, pekerja media berlaku etis karena harus menyampaikan informasi yang dapat dipertanggungjawabkan secara etis. Dasar kode etik yang berlaku untuk pekerja media di Indonesia adalah kode etik organisasi profesi dan kode etik perusahaan. Pekerja media berdasar etika teleologi perlu memperhatikan kepentingan publik. Pekerja media penting untuk mengutamakan kepentingan publik di atas kepentingan lain, karena media merupakan ruang publik yang memungkinkan terciptanya banyak suara dan mengekspresikan berbagai macam pandangan yang berbeda-beda. Berdasarkan perspektif etika keutamaan, konten yang disiarkan di media merupakan refleksi dari nilai-nilai yang dianut individu pekerja media.